Mapping of Graphene Oxide and Single Layer Graphene Flakes—Defects Annealing and Healing - Tsirka, Kyriaki; Katsiki, Antigoni; Chalmpes, Nikolaos; Gournis, Dimitrios; Paipetis, Alkiviadis S. (Frontiers in Materials, 2018)
Graphene has outstanding properties that make it an auspicious material for many applications. This work presents the production of graphene oxide (GO) via the Langmuir – Schaefer process and the subsequent restoration of single layer graphene flakes (SLGF) via the chemical reduction and thermal annealing of the GO. Scanning electron microscopy and optical images were used to evaluate the morphology and surface coverage of the substrate with GO flakes. Through this technique, smooth dispersion; controllable development and population of the GO single flakes on the Si substrate without size limitation have been achieved. The height distribution of the GO was monitored after each processing step by AFM measurements. Additionally, the effects of each process on the structure of the samples was systematically studied via 2D Laser Raman spectroscopy (LRS) mapping. The determination of the layer number on each graphene flake was accomplished by the monitoring of the observed Raman shifts as a function of the position and confirmed via AFM measurements. The spectroscopic analysis of the single flakes was performed in order to study their topography and identify their quality as a function of the processing steps. Via the topographic 2D analysis of both the first and second order vibrational modes as a function of the position on the crystal, the degree of graphitization and /or the presence of defects, as well as the presence of internal stresses were mapped. Such a systematic determination of the effects of reduction and annealing on the structure of single layer graphene samples from reduced GO produced via the Langmuir – Schaefer process is for the first time reported in literature.